ANALISIS HUKUM PERLINDUNGAN PERKAWINAN ANAK DI BAWAH UMUR - Hidayat, Puti (Universitas Wiralodra, 2020)
Related of child marriage, the first one focuses on the age limit of a person. In Indonesia, there is no similarity in the age limit for children, there are still differences. For example, the Civil Code stipulates that the age limit for children is 21 years, Law no. 16 of 2019 concerning Amendments to Law No. 1 of 74 concerning Marriage regulates the age limit of children is l9 years for boys and for girls, while child protection regulates the age limit for children is under 18 years. In this paper, the research methodology is used is the Normative Juridical approach method with data collection techniques by means of literature studies on legal materials, both primary legal materials, secondary legal materials and tertiary legal materials and field studies as a complement. The regulations regarding marriage in this Law concerning the dispensation of a man and a woman to be able to marry under the age of 19, this is based on Article 7 Paragraph (2) of Law No. 16 of 2019 concerning Amendments to Law No. 1 of 1974 concerning Marriage. We know that children are the main legal subject in Law No. 35 of 2014 concerning child protection. It contains restrictions regarding children, namely under 18 years of age. How does the existence of Law No. 35 of 2014 concerning child protection against child marriage? The existence of Law No. 35 of 2015 concerning Child Protection against Underage Marriage as regulated in Article 26 of Law No. 35 of 2015 concerning Child Protection regarding the prohibition of parents from giving permission to their children who are underage in accordance with Article 1 of Law No.35 of 2015 concerning Child Protection, namely a child is someone who is not yet 18 (eighteen) years old, including children who are still in the womb. In addition, Article 76B is further emphasized, namely that every person is prohibited from placing, allowing, involving, ordering to involve children in situations of mistreatment and neglect